2011
DOI: 10.1523/jneurosci.0614-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Input Regulates Spatial and Subtype-Specific Patterns of Neuronal Turnover in the Adult Olfactory Bulb

Abstract: Throughout life, new neurons are added and old ones eliminated in the adult mouse olfactory bulb. Previous studies suggested that olfactory experience controls the process by which new neurons are integrated into mature circuits. Here we report novel olfactoryexperience-dependent mechanisms of neuronal turnover. Using two-photon laser-scanning microscopy and sensory manipulations in adult live mice, we found that the neuronal turnover was dynamically controlled by olfactory input in a neuronal subtype-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(109 citation statements)
references
References 50 publications
13
95
0
Order By: Relevance
“…Second, minocycline treatment does not change the amount of neuroblasts reaching the OB, indicating that minocycline does not affect the SVZ production of neuroblasts. This finding extends previous results showing that odorant deprivation, or olfactory deafferentation, leads to a decreased survival of new OB neurons (Corotto et al, 1994;Petreanu and Alvarez-Buylla, 2002;Yamaguchi and Mori, 2005;Mandairon et al, 2006;Bastien-Dionne et al, 2010;Sawada et al, 2011). From the present study, we conclude that activated microglia is a key regulator capable of adjusting the survival of maturing adultborn OB neurons, at least following chemical lesion of the sensory afferents.…”
Section: Tuning the Survival Of Adult-born Neurons During Ob Inflammasupporting
confidence: 92%
See 1 more Smart Citation
“…Second, minocycline treatment does not change the amount of neuroblasts reaching the OB, indicating that minocycline does not affect the SVZ production of neuroblasts. This finding extends previous results showing that odorant deprivation, or olfactory deafferentation, leads to a decreased survival of new OB neurons (Corotto et al, 1994;Petreanu and Alvarez-Buylla, 2002;Yamaguchi and Mori, 2005;Mandairon et al, 2006;Bastien-Dionne et al, 2010;Sawada et al, 2011). From the present study, we conclude that activated microglia is a key regulator capable of adjusting the survival of maturing adultborn OB neurons, at least following chemical lesion of the sensory afferents.…”
Section: Tuning the Survival Of Adult-born Neurons During Ob Inflammasupporting
confidence: 92%
“…3C). Together, these findings support previous studies showing that sensory deprivation, or olfactory deafferentation, reduces adult OB neurogenesis by decreasing the survival of newly generated neurons (Corotto et al, 1994;Fiske and Brunjes, 2001;Petreanu and AlvarezBuylla, 2002;Yamaguchi and Mori, 2005;Mandairon et al, 2006;Bastien-Dionne et al, 2010;Sawada et al, 2011).…”
Section: The Survival Of New Neurons Decreases After Sensory Deafferesupporting
confidence: 90%
“…Neurotransmission between pre-and postsynaptic fibers in the GL of the OB is extensively modulated by periglomerular interneurons that exclusively express tyrosine TH, CB, or calretinin (CR) (19). Deprivation of presynaptic input from the ONL in rodents, either by treatment with zinc sulfate or by naris occlusion, was previously shown to reduce both TH expression and dopamine levels in the GL of the OB (20,21), whereas naris reopening resulted in the generation of new TH + interneurons (22). We therefore expected that the reduced thickness of the ONL in the OB of Gnao −/− mice would be associated with a reduction in TH expression or a reduced number of TH + periglomerular cells.…”
Section: Resultsmentioning
confidence: 99%
“…4A), we showed that, in live animals, the addition and elimination of periglomerular cells are dynamically controlled by olfactory input in a neuronal subtype-specific manner. 94 To examine the spatiotemporal relationship between lost and replaced neurons, we developed a method for in vivo two-photon laser-ablation of periglomerular cells (Fig. 4B), by which we could selectively eliminate targeted neurons in live animals.…”
Section: Neuronal Maturation and Turnover In The Olfactory Bulbmentioning
confidence: 99%
“…95 Thus, it is possible that adult-born olfactory interneurons show subtype-specific turnover patterns. 94 The turnover of olfactory interneurons is thought to be important for both the maintenance and the plasticity of olfactory functions. Further analysis of the spatiotemporal regulation of neuronal turnover will be needed to understand how neuronal turnover contributes to structural and functional plasticity and/or stability in the adult OB.…”
Section: Neuronal Maturation and Turnover In The Olfactory Bulbmentioning
confidence: 99%